2022
DOI: 10.3390/fermentation8020058
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol Production as an Alternative End for Maple Syrups with Flavor Defects

Abstract: The purpose of this paper is to demonstrate the validity of an alternative route to valorize declassified maple syrups affected by flavor defects such as ropy maple syrup (RMS) and buddy maple syrup (BMS) as feedstocks for ethanol production. An acid hydrolysis treatment (0.1 M, 0.5 M, 5 M, and 10 M) was performed on the RMS to break the polysaccharide chains which are responsible for the flavor defect. The sugars and inhibitors composition of these hydrolysates were analyzed by ion chromatography and ion excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Polyphenols can be extracted from defective syrups using a variety of means without loss of their high-value biological properties [63,64]. Furthermore, the residue remains a good source of sugars for industrial uses such fermentation feedstock or ethanol production [65].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols can be extracted from defective syrups using a variety of means without loss of their high-value biological properties [63,64]. Furthermore, the residue remains a good source of sugars for industrial uses such fermentation feedstock or ethanol production [65].…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of buddy syrup as a carbon source has proven to be an effective and cost-effective approach, showing potential as a feedstock for fermentation. Another study has demonstrated the feasibility of using buddy and ropy maple syrups as potential substrates for fermentation with Saccharomyces cerevisiae to produce ethanol [45]. Moreover, maple syrup has been used as a carbon source in the production of a The utilization of buddy syrup as a carbon source has proven to be an effective and cost-effective approach, showing potential as a feedstock for fermentation.…”
Section: Optimization Of Nutrient Medium By Central Composite Design ...mentioning
confidence: 99%
“…Moreover, maple syrup has been used as a carbon source in the production of a The utilization of buddy syrup as a carbon source has proven to be an effective and cost-effective approach, showing potential as a feedstock for fermentation. Another study has demonstrated the feasibility of using buddy and ropy maple syrups as potential substrates for fermentation with Saccharomyces cerevisiae to produce ethanol [45]. Moreover, maple syrup has been used as a carbon source in the production of a nanobiomaterial, bacterial cellulose, by Acetobacter xylinum BPR 2001 [46].…”
Section: Optimization Of Nutrient Medium By Central Composite Design ...mentioning
confidence: 99%